Culprit-lesion only versus complete multivessel percutaneous intervention in ST-elevation myocardial infarction: A systematic review and meta-analysis of randomized trials. (1st October 2016) - Villablanca, Pedro A.; Briceno, David F.; Massera, Daniele; Hlinomaz, Ota; Lombardo, Marissa; Bortnick, Anna E.; Menegus, Mark A.; Pyo, Robert T.; Garcia, Mario J.; Mookadam, Farouk; Ramakrishna, Harish; Wiley, Jose; et al.
Abstract: Background: ST-segment elevation myocardial infarction (STEMI) in patients with concomitant multivessel (MV) coronary artery disease (CAD) is associated with poor outcomes. Percutaneous coronary intervention (PCI) of the culprit-lesion only (CLO) as compared with a MV PCI approach to revascularization remains uncertain. Our objective is to gain a better understanding of the efficacy and safety of CLO as compared with MV PCI in patients with STEMI by conducting an updated meta-analysis. Methods: A comprehensive search of PubMed, CENTRAL, EMBASE, The Cochrane Central Register, theClinicalTrials.gov Website, and Google Scholar databases of randomized controlled trials (RCTs) was performed. Results: Seven RCTs were included, enrolling a total of 2006 patients. We found that there was a significant reduction in major adverse cardiovascular events (MACE) (OR, 0.62; 95% CI, 0.43–0.90), cardiovascular mortality (OR, 0.46; 95% CI, 0.27–0.80), and repeat revascularization (RRV) (OR, 0.39; 95% CI, 0.30–0.51) favoring MV over the CLO approach for patients undergoing primary PCI. The number needed to treat in order to prevent one CV mortality, RRV, or MACE event is 47, 11, and 16 patients, respectively. No differences were observed between MV vs. CLO PCI for subsequent myocardial infarction (OR, 0.74; 95% CI, 0.40–1.39), all-cause mortality (OR, 0.78; 95% CI, 0.53–1.15), non-cardiovascular mortality (OR, 1.35; 95% CI, 0.74–2.48), all-bleeding events (OR, 0.82; 95% CI, 0.40–1.65), contrast-induced nephropathy (OR, 0.72; 95% CI, 0.33–1.54), and stroke (OR, 1.28; 95% CI, 0.47–3.46). Conclusions: MV PCI significantly reduces the rate of MACE, CV mortality, and RRV without significant harm as compared to CLO PCI. Highlights: MV PCI in STEMI is associated with reduction in CV mortality, MACE, and repeat revascularization. MV PCI in STEMI is not associated with increased risk of stroke, CIN, or bleeding complications. The appropriate timing of non-culprit-lesion PCI has yet to be definitively defined.